Understanding Second Language Performance: The Significance of Personality Type Among Learners - Ady, Rizky Phalosa; Mardiah, Zaqiatul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
According to studies, MBTI personality types exhibit different cognitive function preferences, where a strong inclination towards certain traits can influence how well individuals receive and process information. This is related to intelligence and problem-solving abilities, including the impact on foreign language learning. Understanding the role of personality traits in language learning can significantly enhance educational strategies. Despite growing interest in personalized education, the influence of personality on language acquisition remains underexplored, particularly for Arabic learners. Our research examines the impact of the MBTI personality dimensions of introversion and intuition on Arabic language performance as a second language among Indonesian students. We studied 53 college students majoring in Arabic language-related fields. Using the Myers-Briggs Type Indicator (MBTI) and an Arabic language proficiency test, we conducted data analysis through multiple linear regression, ensuring robustness with assumption tests for residual normality, multicollinearity, and heteroscedasticity. The results indicated that the introversion and intuition dimensions of the MBTI did not significantly affect Arabic language performance (F-test: Sig. 0.696 > 0.05 and t-test 0.411, 0.754 > 0.05). These findings suggest that introversion and intuition may not be critical factors in Arabic L2 proficiency. This research provides insights for the development of Arabic language teaching programs, emphasizing that factors other than personality may play a more significant role in language performance. However, the complex relationship between personality and language learning warrants further investigation to fully understand the dynamics at play.